2018
DOI: 10.1159/000489862
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Effects of CD40 and CD86 Silencing in Dendritic Cells on the Control of Allergic Diseases

Abstract: Background: We previously reported that siRNA-induced CD40-silenced dendritic cells (DCs) inhibit allergic responses and symptoms. However, more potent therapies are needed. To our knowledge, synergic effects of gene silencing in DCs by ≥2 siRNAs have not been reported to control allergic diseases. Therefore, we investigated the synergistic effects of the silencing of CD40 and CD86 in DCs on allergic responses. Methods: Mice were treated with CD40/CD86-silenced DCs, which were transfected with CD40/CD86 siRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
(36 reference statements)
0
11
1
Order By: Relevance
“…DCs were generated from bone marrow progenitor cells of 6-to 8-week-old male BALB/c mice (Japan SLC, Shizuoka, Japan), as previously reported. 11 , 19 , 20 , 21 Briefly, bone marrow cells were flushed from the femurs and tibias and cultured. DCs (CD40-silenced DCs) were transfected with siRNA against CD40 (CD40 siRNA, UUCUCAGCCCAGUGGAACA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DCs were generated from bone marrow progenitor cells of 6-to 8-week-old male BALB/c mice (Japan SLC, Shizuoka, Japan), as previously reported. 11 , 19 , 20 , 21 Briefly, bone marrow cells were flushed from the femurs and tibias and cultured. DCs (CD40-silenced DCs) were transfected with siRNA against CD40 (CD40 siRNA, UUCUCAGCCCAGUGGAACA).…”
Section: Methodsmentioning
confidence: 99%
“…OVA-specific T-cell responses were estimated as previously reported. 21 Lymphoid cells (2 × 10 6 cells/mL) from the cervical lymph nodes and spleen were cultured with OVA (100 μg/mL) at 37 °C for 72 h, after which the culture supernatants were collected.…”
Section: Methodsmentioning
confidence: 99%
“…13,14 Transfection of CD40 siRNA (1 mg) and CD86 siRNA (1 mg) into DCs was also performed as previously described. 8,15,16 Immunization and Treatment CD40-silenced OVA B cells (5 Â 10 6 cells/mouse), CD86silenced OVA B cells (5 Â 10 6 cells/mouse), CD40-/ CD86-silenced OVA B cells (5 Â 10 6 cells/mouse), CD40-/CD86-silenced OVA DCs (5 Â 10 6 cells/mouse), control B cells (CD40-expressing B cells, 5 Â 10 6 cells/ mouse), or phosphate-buffered saline (PBS) alone were injected intravenously into 7-week-old male BALB/c mice on day 1. These mice were sensitized with intraperitoneal OVA (10 lg) and 2 mg Al (OH) 3 on days 2 and 16.…”
Section: Sirna and Gene Silencingmentioning
confidence: 99%
“…7 We also reported that CD40-silenced B cells inhibited allergic responses and symptoms. 8 However, more potent therapies are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation